Physical fitness, physical activity, exercise training and cognitive function in older adults - Tomohiro Okura; Mahshid Saghazadeh; Yuki Soma; Kenji Tsunoda (Japanese Society of Physical Fitness and Sports Medicine, 2013)
Cognitive impairment is a major health and social issue. Over the past decade many studies have reported that engaging in physical activity and exercise training, and a higher level of physical fitness, can postpone the onset of age-associated cognitive decline or reduce its impact. In this review, therefore, we focused on the association between physical fitness, physical activity, exercise training and cognitive function in older adults. It is assumed that physical fitness, including cardiorespiratory fitness, muscle strength, walking ability, balance, reaction time and flexibility are associated with cognitive function. When considering potential determinants of age-associated cognitive decline, active lifestyles are often considered as protective. In recent years, some regular forms of exercise, including resistance training, have been reported as providing potentially useful psychological benefits. More recently, several potential mechanisms that may underlie the association between physical activity or exercise training and reduced risk of cognitive decline have been revealed.